(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: The fallopian tubes act as conduit for spermatozoa to reach the oocyte and to convey the fertilized (egg) to enter the uterine cavity following fertilization. Problems with the fallopian tubes can lead to infertility. Detailed morphological and histological knowledge is essential for the diagnosis and management of fallopian tube disease. Objective: The purpose of the present study was to identify the inner diameter of ampulla of the fallopian tube and its changes with advancing age. Methodology: This descriptive cross-sectional study was conducted in the Department of Anatomy at Dhaka Medical College, Dhaka, Bangladesh from July 2008 to June 2009 for a period of one (01) year. This present study was performed on post mortem fallopian tubes of Bangladeshi female. Among them lowest age was 12 years and highest age was 50 years. Samples were divided into three differential age groups named asgroup A (10 to 13 years), group B (14 to 45 years), and group C (46 to 50 years). All samples were studied morphologically and histologically. Results: The mean inner diameter of the ampulla of the right and left fallopian tubes ranged from 1.99±0.08 to 3.24±0.27 mm. The difference between all the groups were statistically significant (p < 0.001). Conclusion: The mean difference of the inner diameter of the ampulla of the right and left fallopian tubesbetween groupA and groupB and groupB and groupC were statistically significant; however, there was no significant difference between right and left fallopian tube. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 137-140